Correlation of C- Reactive Protein (CRP) and Lipid Profile Among Patients of Ischemic Heart Disease (IHD) and Non-Ischemic Heart Disease Patients - Anwer, Muhammad Shahzad; Khalid, Usama Bin; Khan, Sara; Ali, Shamshad; Nizamani, Mohsin Hussain; Saeed, Rabia (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine correlation of C-reactive protein with lipid profile among patients of ischemic heart disease (IHD) and non-ischemic heart disease (non-IHD) and to determine association of CRP with dyslipidemia in IHD and non-IHD patients.Place and Duration of Study: Combined Military Hospital, Bahawalpur Pakistan, from Apr 2023 to Dec 2023.Study Design: Comparative cross sectional study.Methodology: A total of 252 patients were enrolled in this study (159 patients of IHD and 93 non-IHD patients). Quantitative CRP and serum Lipid Profile were assayed on fully automated chemistry analyzer Cobas c501 by Roche®. Pearson correlation technique was applied to determine correlation. Chi square test was used to find any significant association between CRP and both IHD and non-IHD groups.Results: Out of 252 patients, 159(63.1%) had IHD, while 93(36.9%) had no history of IHD. For IHD group mean of total cholesterol, triglycerides, LDL-cholesterol, HDL-cholesterol and CRP were 5.71±0.70 mmol/L, 2.48±0.79 mmol/L, 3.03±0.60 mmol/L, 1.11±0.25 mmol/L and 11.04±5.92 mg/L respectively. Pearson correlation coefficient (r) between CRP and total cholesterol, TG, LDL-cholesterol and HDL-cholesterol were 0.84, 0.46, 0.73 and -0.79 for IHD group, while these were 0.42, 0.02, 0.29 and - 0.38 respectively for non-IHD group. Strong association of CRP among IHD and Non-IHD groups with dyslipidemia was observed (p